SAT0609 Giant cell arteritis: atherosclerosis as pitfall in the halo sign. (15th June 2017) - Miguel, E De; Beltran, LM; Deodati, F; Monjo, I; Schmidt, WA; García-Puig, J
Abstract : Background: The halo sign (defined as an homogenous, hypoechoic wall thickening, well delineated towards the luminal side, visible in longitudinal and transverse planes). is the more accurate ultrasonographic (US) finding for the diagnosis of Giant Cell Arteritis (GCA). False-positive halos are seen in malignant and infectious diseases. The new US high frequencies probes make possible not only to see the halo sign but also measure the increase of the intima-media-thickness (IMT). Moreover, the US appearance of the IMT in atherosclerotic carotid artery may be hypoechoic as the halo sign. Objectives: The aim of this study was to explore if the increase of the atherosclerotic IMT can mimic the halo sign in temporal arteries (TA) and to produce false positives in the diagnosis of GCA. Methods: Consecutive non selected patients, ≥50 years-old with high vascular risk according to European Guidelines on Cardiovascular Disease Prevention, and without signs or symptoms of GCA, were included. Ultrasonography of carotid artery: Carotid ultrasound examinations were performed on a Mylab Seven (Esaote Medical Systems, Italy) with a 4–13 MHz linear-array. The system employed dedicated software radiofrequency-tracking technology to obtain IMT (QIMT®). Ultrasonography of temporal superficial artery: A color Doppler ultrasound (CDU) and grey scale measure of the IMT/halo sign in the branches of both TA was performed by a second experienced sonographer. A Mylab Twice equipment (Esaote, Geneve, Italy) was used, with a 22 MHz frequency for grey scale and a 12.5 MHz for CDU, with a color gain of 51 and a PRF of 2 kHz. The sonographer was blind to the clinical data and carotid ultrasound IMT measures. Examination videos were stored for reliability and an intra-reader was performed months after the examination. Statistical analysis: Descriptive frequencies, Student's t -test, Cronbach's alpha and Spearman correlations was used. Results: Forty patients were studied, 28 men (70%), with a mean age of 70, 6±6, 9 years. Three patients were active smoker and 27 ex-smokers. Arterial hypertension was present in 39 (97.5%), dyslipidemia in 34 (85%) and diabetes in 19 (47.5%). The mean erythrocyte sedimentation rate was 13.6±11.0. Eighty carotids were studied, 50 had plaques and 30 did not with a IMT ranged from 0.528 to 1.480 mm. The mean values of TA related with the carotid IMT are presented in the table: the increase in the carotid IMT is associated with an increase in the IMT of the TA with a weak Spearman correlation (parietal branches 0.282 p=0.012 and frontal branches 0.228 p=0.048). From reliability a Cronbach's alpha of 0.900 and 0.876 were achieved for parietal and frontal branches respectively. Some patients had a TA IMT that can be interpreted as halo sign: 18 (45%) patients and 33 (20.6%) TA branches if we choose a cutoff >0.30 mm of IMT/halo sign; 4 (10%) patients and 7 (4.4%) TA branches if the cutoff were >0.34 mm. Conclusions: The atherosclerotic disease can produce false-positive GCA diagnosis. Carotid IMT >0.9 mm is associated with halo sign in TA. The IMT cutoff value for the diagnosis of GCA should be established. Disclosure of Interest: None declared